Türk Vatandaşlığı Kanununun Uygulanmasına İlişkin Yönetmeliğin 72/5. Maddesinin Kanunilik İlkesi ve Hükmün Açıklanmasının Geri Bırakılması Bağlamında Değerlendirilmesi - (:unkn) unknown (My University, 2019)
Türk vatandaşlığının sonradan kazanılmasında aranan “milli güvenlik ve kamu düzeni bakımından engel teşkil edecek bir hali bulunmama” şartından ne anlaşılması gerektiği Türk Vatandaşlık Kanunu Uygulama Yönetmeliği m.72/5’te ortaya konulmuştur. İlgili kavramlar somutlaştırılırken Türk Vatandaşlık Kanununda ve onun gerekçesinde yer almayan ilave şart-lar getirilmiştir. Getirilen bu ilave şartların içerisinde, taksirli suçlar hariç olmak üzere altı aydan fazla hapis cezası alan yabancı gerçek kişilerin hükmün açıklanması geri bırakılsa bile Türk vatandaşlığını kazanamayacağı yer almıştır. Bahse konu bu düzenleme hem kanunîlik ilkesine hem de hükmün açıklanmasının geri bırakılması düzenlemesinin düzenleniş amacına aykırılık teşkil etmektedir.

What should be understood from the condition of "should not have any obstacle in terms of national security and public order" in acquiring the Turkish citizenship is explained in the Article 72/5 of the Regulation on the Implementation of the Turkish Citizenship Law. While embodying relevant concepts, additional requirements which do not exist in the Turkish Citizenship Law and its justification have been introduced in the Regulation. Pursuant to additional conditions, foreign real persons are not able to gain Turkish citizenship if foreign real persons were sentenced to imprisonment for a period of more than six months even if deferment of the announcement of the verdict, except for negligence crimes. This regulation contradicts both the principle of legality and the objection of deferment of the announcement of the verdict.
Examining the Article 72/5 of the Regulation on the Implementation of the Turkish Citizenship Law in the Context of the Principle of Legality and Deferment of the Announcement of the Verdict
Keywords: Hukuk